ON THE ISSUE ABOUT THE EFFECTIVENESS OF NARRATIVE ADVERTISING IN POPULAR SCIENCE JOURNALS - E. V. Shcherbakova; D. M. Belugina; E. V. Zvonova (Вестник университета, 2020)
The issue of studying the effectiveness of advertising in popular science journals does not occupy a large place in scientific research. This state of affairs is challenging, since the activities of popular science journals are aimed at attracting the attention and interest of young people, creative and active potential, to science issues. The effectiveness of narrative advertising as a social-psychological communication technology has been examined in the article. The research has been carried out within the framework of a semiotic approach. The results of the research of narrative advertising texts, in which young people engaged in scientific activities and young people whose professional functionality is not related to scientific research took part, have been described. The toolkit used made it possible to identify differences between the perception of narrative advertising texts by two groups of respondents and also similar trends in the perception of texts, which suggests a possibility of developing an effective advertising strategy for promoting a popular science magazine. The research results may be of interest for professionals working in the field of advertising, especially in the field of advertising of intellectual services.